Use of Multicomponent Cryoprotective Media During Cryopreservation of Murine Embryos by Vitriï¬cation - Shakhova , Yuliia; Paliy , Anatoliy; Paliy, Andriy; Shigimaga , Victor; Kis, Victor; Ivanov , Volodymyr (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(2): 203-206